Protection of Data Privacy under Digital Personal Data Protection Act, 2023: A Critical Legal Analysis - Mujibur Rehman; Maria Momin (AG Volumes, 2026)
Data privacy is an increasingly significant and complex issue in today’s digital age. It is a fundamental aspect of our digital lives, protecting our personal information from misuse and abuse. In India, the Digital Personal Data Protection Act of 2023 marks a significant milestone in the evolving landscape of data privacy and protection. It is designed to tackle the growing concerns surrounding the handling of personal data in the digital age. It sets forth a comprehensive framework that empowers individuals with greater control over their personal information. Central to this Act is the acknowledgment of data privacy as a fundamental right, in alignment with international standards and best practices. While Digital Personal Data Protection Act of 2023 is a substantial leap forward in safeguarding data privacy, nevertheless, challenges persist. Balancing the needs of innovation and business with the imperatives of data protection remains an ongoing concern. Moreover, effectiveness of the Digital Personal Data Protection Act of 2023 signifies a crucial step toward fortifying data privacy rights in the digital era. By codifying fundamental principles and establishing stringent mechanisms for enforcement, it aims to protect individuals’ personal data while fostering a conducive environment for innovation and technology-driven growth. Its impact will depend on rigorous implementation and continuous adaptation to the dynamic landscape of digital data. In this chapter, the authors critically analyse the personal data breaches by regulatory authority and aim to build a data protection framework that would regulate processing of personal data by government and non-government entities in light of right to privacy judgment under the Digital Personal Data Protection Act, 2023